Steel material
By controlling the number density of Bi particles in steel and combining specific chemical composition, the melting and thermal processing and fracture of steel during high-frequency quenching and thermal processing are solved, and the fatigue strength of mechanical structure components is improved.
Patent Information
- Application Number
- CN202380054041.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-07-14
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to suppress melting and thermally processed rupture of steel during high-frequency quenching, and the machinability of the steel is insufficient, affecting the fatigue strength of the components for mechanical structures.
Steel with specific chemical composition is adopted, containing elements such as C, Si, Mn, Bi, etc., and by controlling the number density of Bi particles at different depths, the steel has excellent melt fracture resistance and heat-process fracture resistance in the surface area and high machinability in the internal area.
The crack resistance and machining properties of steel during high-frequency quenching and thermal processing are improved, thereby improving the fatigue strength of mechanical structure components.
Smart Images

Figure CN119585457A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a steel material, and more particularly, to a steel material used as a raw material of a machine structural component. Background Art
[0002] Mechanical structural parts can be used in automobile parts such as crankshafts of automobiles and engineering vehicles. Mechanical structural parts require very high fatigue strength.
[0003] For example, Japanese Patent Application Laid-Open No. 2008-169411 (Patent Document 1) discloses a technique for improving the fatigue strength of a machine structural component.
[0004] The steel material used as the raw material of the machine structural parts disclosed in Patent Document 1 contains, by mass%, C: 0.15-0.55%, Si: 0.01-2.0%, Mn: 0.01-2.5%, Cu: 0.01-2.0%, Ni: 0.01-2.0%, Cr: 0.01-2.5%, Mo: 0.01-3.0%, and at least one selected from V and W: 0.01-1.0% in total, and the balance is Fe and inevitable impurities. The steel material is soaked at 1010°C to 1050°C, cooled to 500°C to 550°C at a cooling rate of 200°C / min or more, then cooled to 150°C or less at a cooling rate of 100°C / min or more, and then heated in the temperature range of 550°C to 700°C, and the LMP giving the maximum value of HRC hardness at room temperature is 17.66 or more. In this document, LMP, which gives the maximum value of the HRC hardness at room temperature after heat treatment under the above conditions, is set to 17.66 or more, and softening resistance is improved, thereby improving fatigue properties.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-169411 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Incidentally, in order to improve the fatigue strength of machine structural parts, surface hardening treatment is sometimes performed on the machine structural parts.
[0010] One of the various surface hardening treatments is high frequency quenching. High frequency quenching can harden only the required parts. High frequency quenching forms a hardened layer on the surface of the steel after heating at high temperature and then cooling. Compared with other surface hardening treatments such as nitrocarburizing, high frequency quenching can obtain a large hardened layer depth and high fatigue strength.
[0011] Taking the case where the mechanical structural component is a crankshaft as an example, the high-frequency quenching treatment performed on the mechanical structural component will be described. Figure 1 In the case of the shape shown, in order to improve the fatigue strength of the crankshaft, for example, the chamfered R portion 1 of the crankshaft is subjected to high-frequency quenching. In this case, a hardened layer is formed on the surface layer of the chamfered R portion 1.
[0012] In order to increase the depth of the hardened layer, in high frequency quenching, it is sufficient to increase the output of high frequency power and raise the heating temperature. However, when high frequency quenching is performed at a high temperature, the heating temperature tends to be excessively high at the edge of the mechanical structural component. For example, in the case of a mechanical structural component Figure 1 In the case of the crankshaft shown, the heating temperature becomes excessively high at the edge portion 2. In particular, when the heating rate during induction hardening is fast, the heating temperature tends to become excessively high.
[0013] For example, when the heating temperature during high-frequency quenching becomes excessively high and reaches 1350°C or higher, a part of the steel material melts and cracks. Hereinafter, in this specification, such cracks are referred to as "melt cracks". It is preferable to suppress the occurrence of such melt cracks. In other words, excellent resistance to melt cracks is required for steel materials.
[0014] In addition, for steel materials that become raw materials for mechanical structural parts, hot working is performed in the manufacturing process of mechanical structural parts or in the manufacturing process of steel materials. Therefore, it is required to suppress the occurrence of cracks caused by hot working (hot working cracks) for steel materials. In other words, excellent resistance to hot working cracks is required for steel materials.
[0015] In addition, steel materials that are raw materials for machine structural parts are subjected to cutting in the manufacturing process of the machine structural parts. Sometimes, excellent cutting performance is required, especially inside the steel material. For example, when the machine structural part is a crankshaft, processing such as drilling is performed on the center part of both end faces. Therefore, excellent cutting performance is required inside the steel material.
[0016] In the above-mentioned Patent Document 1, the melting crack resistance, hot working crack resistance and machinability of the steel material are not studied.
[0017] An object of the present disclosure is to provide a steel material having excellent resistance to melt cracking, excellent resistance to hot working cracking, and excellent machinability, and which can obtain high fatigue strength for machine structural parts when used as a material for machine structural parts.
[0018] Solutions to the problem
[0019] The steel material disclosed in the present invention is a steel material having a circular cross section perpendicular to the axial direction.
[0020] The chemical composition of the steel material includes the following in mass %:
[0021] C: more than 0.30% and less than 0.60%,
[0022] Si: 0.01-0.90%,
[0023] Mn: 0.50-1.70%,
[0024] P: 0.030% or less,
[0025] S: 0.200% or less,
[0026] Bi: 0.0051~0.2500%,
[0027] Al: 0.001~0.100%,
[0028] N: 0.0250% or less,
[0029] O: 0.0050% or less,
[0030] Cr: 0~1.30%,
[0031] V: 0~0.200%、
[0032] Sn: 0~0.1000%,
[0033] Sb: 0~0.0500%,
[0034] As: 0~0.0500%、
[0035] Pb: 0~0.09%,
[0036] Mg: 0~0.0100%,
[0037] Ti: 0~0.0400%,
[0038] Nb: 0~0.0500%,
[0039] W: 0~0.4000%、
[0040] Zr: 0~0.2000%,
[0041] Ca: 0~0.0100%,
[0042] Te: 0~0.0100%,
[0043] B: 0~0.0050%,
[0044] Rare earth elements: 0~0.0100%,
[0045] Co: 0~0.0100%,
[0046] Se: 0~0.0100%,
[0047] In: 0~0.0100%,
[0048] Mo: 0~0.30%,
[0049] Cu: 0-0.50%,
[0050] Ni: 0 to 0.50%, and
[0051] The balance is Fe and impurities.
[0052] Fn defined by formula (1) is 0.45 to 1.05,
[0053] When the radius of the steel material is defined as R, at a depth of 0.08R from the surface of the steel material,
[0054] The number density of fine Bi particles is 15.00 / mm 2 In the above, the fine Bi particles are Bi particles having an equivalent circle diameter of 0.1 to 1.0 μm.
[0055] The number density of coarse Bi particles is 0.25 / mm 2 Hereinafter, the coarse Bi particles are Bi particles having an equivalent circle diameter of 10.0 μm or more.
[0056] At a depth of 0.65R from the surface of the above steel material,
[0057] The number density of the fine Bi particles is less than 15.00 / mm 2 ,
[0058] The number density of the above-mentioned coarse Bi particles exceeds 0.25 / mm 2 .
[0059] Fn=C+(Si / 10)+(Mn / 5)-(5S / 7)+(5Cr / 22)+1.65V (1)
[0060] Here, the content of the corresponding element in mass % is substituted into each element symbol in formula (1), and when the element is not contained, "0" is substituted into the corresponding element symbol.
[0061] Effects of the Invention
[0062] The steel material disclosed in the present invention has excellent resistance to melt cracking, excellent resistance to hot working cracking, and excellent machinability, and when used as a material for machine structural parts, the machine structural parts can obtain high fatigue strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a front view of a portion of a crankshaft as an example of a machine structural component.
[0064] Figure 2 This is a cross-sectional view perpendicular to the axial direction of the steel material according to the present embodiment.
[0065] Figure 3 This is a schematic diagram of the microstructure in the melt fracture evaluation test in the examples.
[0066] Figure 4 The melt fracture evaluation test in the examples is Figure 3 Schematic representation of different microstructures.
[0067] Figure 5 This is a side view of a fatigue test piece used in the fatigue strength evaluation test of the example.
[0068] Explanation of symbols
[0069] 1 Chamfer R part
[0070] 2 Crankshaft edge
[0071] 15 Melt fracture DETAILED DESCRIPTION
[0072] First, the inventors studied the chemical composition of a steel material that improves the fatigue strength of a machine structure component when used as a raw material for the machine structure component. As a result, the inventors believed that if a steel material having the following chemical composition contains, in terms of mass%, C: more than 0.30% and less than 0.60%, Si: 0.01 to 0.90%, Mn: 0.50 to 1.70%, P: less than 0.030%, S: less than 0.200%, Al: 0.001 to 0.100%, N: less than 0.0250%, O: less than 0.0050%, Cr: 0 to 1.30%, V: 0 to 0.200%, Sn: 0 to 0.1000%, Sb: 0 ~0.0500%, As: 0~0.0500%, Pb: 0~0.09%, Mg: 0~0.0100%, Ti: 0~0.0400%, Nb: 0~0.0500%, W: 0~0.4000%, Zr: 0~0.2000%, Ca: 0~0.0100%, Te: 0~0.0100%, B: 0~0.0050%, rare earth elements: 0~0.0100%, Co: 0~0.0100%, Se: 0~0.0100%, In: 0~0.0100%, Mo: 0~0.30%, Cu: 0~0.50%, Ni: 0~0.50%, and the balance is Fe and impurities.
[0073] Next, the inventors of the present invention studied a method for improving the machinability of a steel material having the content of each element in the chemical composition within the above range. As a result, the inventors of the present invention found that by setting Fn defined by formula (1) to 0.45 to 1.05, excellent fatigue strength can be obtained for machine structural parts, and the machinability of the steel material as a raw material for machine structural parts is improved.
[0074] Fn=C+(Si / 10)+(Mn / 5)-(5S / 7)+(5Cr / 22)+1.65V (1)
[0075] The present inventors further studied a method for improving the resistance of steel materials to melt cracking during induction hardening.
[0076] The C content affects the melt fracture of the steel during high-frequency quenching. Specifically, due to the C segregated at the grain boundaries, the melting point at the grain boundaries will be lowered. As a result, melt fracture is likely to occur. Therefore, 0.0051 to 0.2500% Bi is further contained in the above-mentioned chemical composition. If Bi is contained in the above-mentioned range, Bi particles (inclusions) are generated in the steel. The fine Bi particles suppress the coarsening of the grains (austenite grains) in the steel during high-frequency quenching through the pinning effect. If the grains can be kept fine during high-frequency quenching, the reduction in the grain boundary area can be suppressed. If the reduction in the grain boundary area can be suppressed and a certain degree of grain boundary area can be ensured, the average C concentration segregated at the grain boundary per unit area is reduced. As a result, the occurrence of melt fracture can be suppressed.
[0077] However, when the steel contains Bi in the above range, not only fine Bi particles but also coarse Bi particles are generated. Coarse Bi particles become the starting point of hot working cracking. Therefore, if the coarse Bi particles are excessively present, the heat working cracking resistance of the steel is reduced.
[0078] On the other hand, coarse Bi particles improve the machinability of the steel. Considering the above, it is considered that it is difficult to simultaneously obtain excellent resistance to melt cracking, excellent resistance to hot working cracking, and excellent machinability by containing Bi in the above range in the steel having the above chemical composition.
[0079] However, the inventors of the present invention believe that by changing the number density of fine Bi particles and the number density of coarse Bi particles according to the region of the steel material, it is possible to simultaneously obtain excellent resistance to melt cracking, excellent resistance to heat working cracking, and excellent machinability. Specifically, in the steel material, the surface region of the steel material is prone to melt cracking and heat working cracking. Therefore, it is sufficient as long as excellent resistance to melt cracking and excellent resistance to heat working cracking can be obtained in the surface region of the steel material. On the other hand, melt cracking and heat working cracking are not likely to occur in the internal region of the steel material. Therefore, it is sufficient as long as high machinability can be obtained in the internal region of the steel material.
[0080] Based on the above technical ideas, the inventors investigated and studied the relationship between the number density of fine Bi particles and the number density of coarse Bi particles in the surface region and the internal region of the steel material and the resistance to melting cracking, resistance to hot working cracking and machinability of the steel material. As a result, the inventors found that for a steel material satisfying the above chemical composition and Fn of 0.45 to 1.05, if the number density of fine Bi particles in the surface region is 15.00 pcs / mm 2 The number density of coarse Bi particles is 0.25 / mm 2 Below, the number density of fine Bi particles in the inner region is less than 15.00 pcs / mm2 、The number density of coarse Bi particles exceeds 0.25 / mm 2 , it is possible to simultaneously satisfy excellent resistance to melt cracking, excellent resistance to hot working cracking and excellent machinability. Furthermore, when used as a raw material for machine structure parts, excellent fatigue strength can be obtained in the machine structure parts.
[0081] The steel material of the present embodiment completed based on the above technical ideas has the following configuration.
[0082] [1] A steel material having a circular cross section perpendicular to an axial direction,
[0083] The chemical composition of the above steel material is composed of the following elements in mass %:
[0084] C: more than 0.30% and less than 0.60%,
[0085] Si: 0.01-0.90%,
[0086] Mn: 0.50-1.70%,
[0087] P: 0.030% or less,
[0088] S: 0.200% or less,
[0089] Bi: 0.0051~0.2500%,
[0090] Al: 0.001~0.100%,
[0091] N: 0.0250% or less,
[0092] O: 0.0050% or less,
[0093] Cr: 0~1.30%,
[0094] V: 0~0.200%、
[0095] Sn: 0~0.1000%,
[0096] Sb: 0~0.0500%,
[0097] As: 0~0.0500%、
[0098] Pb: 0~0.09%,
[0099] Mg: 0~0.0100%,
[0100] Ti: 0~0.0400%,
[0101] Nb: 0~0.0500%,
[0102] W: 0~0.4000%、
[0103] Zr: 0~0.2000%,
[0104] Ca: 0~0.0100%,
[0105] Te: 0~0.0100%,
[0106] B: 0~0.0050%,
[0107] Rare earth elements: 0~0.0100%,
[0108] Co: 0~0.0100%,
[0109] Se: 0~0.0100%,
[0110] In: 0~0.0100%,
[0111] Mo: 0~0.30%,
[0112] Cu: 0-0.50%,
[0113] Ni: 0 to 0.50%, and
[0114] The balance is made up of Fe and impurities.
[0115] Fn defined by formula (1) is 0.45 to 1.05,
[0116] When the radius of the steel material is defined as R, at a depth of 0.08R from the surface of the steel material,
[0117] The number density of fine Bi particles is 15.00 / mm 2 In the above, the fine Bi particles are Bi particles having an equivalent circle diameter of 0.1 to 1.0 μm.
[0118] The number density of coarse Bi particles is 0.25 / mm 2 Hereinafter, the coarse Bi particles are Bi particles having an equivalent circle diameter of 10.0 μm or more.
[0119] At a depth of 0.65R from the surface of the above steel material,
[0120] The number density of the fine Bi particles is less than 15.00 / mm 2 ,
[0121] The number density of the above-mentioned coarse Bi particles exceeds 0.25 / mm 2 ,
[0122] Fn=C+(Si / 10)+(Mn / 5)-(5S / 7)+(5Cr / 22)+1.65V (1)
[0123] Here, the content of the corresponding element in mass % is substituted into each element symbol in formula (1), and when the element is not contained, "0" is substituted into the corresponding element symbol.
[0124] [2] The steel material according to [1], wherein
[0125] The above chemical composition contains one or more elements selected from the following:
[0126] Cr: 0.01~1.30%,
[0127] V: 0.001~0.200%,
[0128] Sn: 0.0001~0.1000%,
[0129] Sb: 0.0001~0.0500%,
[0130] As: 0.0001~0.0500%,
[0131] Pb: 0.01~0.09%,
[0132] Mg: 0.0001~0.0100%,
[0133] Ti: 0.0001~0.0400%,
[0134] Nb: 0.0001~0.0500%,
[0135] W: 0.0001~0.4000%、
[0136] Zr: 0.0001~0.2000%,
[0137] Ca: 0.0001~0.0100%,
[0138] Te: 0.0001~0.0100%,
[0139] B: 0.0001~0.0050%,
[0140] Rare earth elements: 0.0001~0.0100%,
[0141] Co: 0.0001~0.0100%,
[0142] Se: 0.0001~0.0100%,
[0143] In: 0.0001~0.0100%,
[0144] Mo: 0.01~0.30%,
[0145] Cu: 0.01~0.50%,
[0146] Ni: 0.01~0.50%.
[0147] Hereinafter, the steel material of the present embodiment will be described in detail. "%" of an element means mass % unless otherwise specified.
[0148] [Features of the Steel Material of the Present Embodiment]
[0149] The steel material of the present embodiment satisfies the following features 1 to 4.
[0150] (Feature 1)
[0151] The chemical composition includes, by mass%, C: more than 0.30% and less than 0.60%, Si: 0.01-0.90%, Mn: 0.50-1.70%, P: less than 0.030%, S: less than 0.200%, Bi: 0.0051-0.2500%, Al: 0.001-0.100%, N: less than 0.0250%, O: less than 0.0050%, Cr: 0-1.30%, V: 0-0.200%, Sn: 0-0.1000%, Sb: 0-0.0500%, As: 0-0.0500%, Pb: 0-0 .09%, Mg: 0~0.0100%, Ti: 0~0.0400%, Nb: 0~0.0500%, W: 0~0.4000%, Zr: 0~0.2000%, Ca: 0~0.0100%, Te: 0~0.0100%, B: 0~0.0050%, rare earth elements: 0~0.0100%, Co: 0~0.0100%, Se: 0~0.0100%, In: 0~0.0100%, Mo: 0~0.30%, Cu: 0~0.50%, Ni: 0~0.50%, and the balance is Fe and impurities.
[0152] (Feature 2)
[0153] Fn defined by formula (1) is 0.45 to 1.05.
[0154] (Feature 3)
[0155] When the radius of the steel is defined as R, the number density of fine Bi particles at a depth of 0.08R from the surface of the steel is 15.00 particles / mm. 2 The number density of coarse Bi particles is 0.25 / mm 2Hereinafter, the fine Bi particles are Bi particles having an equivalent circle diameter of 0.1 to 1.0 μm, and the coarse Bi particles are Bi particles having an equivalent circle diameter of 10.0 μm or more.
[0156] (Feature 4)
[0157] At a depth of 0.65R from the surface of the steel, the number density of fine Bi particles is less than 15.00 / mm 2 , the number density of coarse Bi particles exceeds 0.25 / mm 2 .
[0158] Hereinafter, features 1 to 4 will be described.
[0159] [About (Feature 1) Chemical composition]
[0160] The chemical composition of the steel material of the present embodiment contains the following elements.
[0161] C: more than 0.30% and less than 0.60%
[0162] Carbon (C) increases the hardness of machine structural parts made of steel materials and improves the fatigue strength of machine structural parts. If the C content is 0.30% or less, the above effects cannot be fully obtained even if the contents of other elements are within the range of this embodiment.
[0163] On the other hand, C lowers the melting point of the steel material. Therefore, if the C content exceeds 0.60%, even if the contents of other elements are within the range of the present embodiment, the steel material is prone to melt fracture when high-frequency quenching is performed on the steel material in the manufacturing process of the machine structure parts using the steel material as the raw material.
[0164] Therefore, the C content exceeds 0.30% and is 0.60% or less.
[0165] The lower limit of the C content is preferably 0.31%, more preferably 0.35%, further preferably 0.37%, further preferably 0.38%.
[0166] The upper limit of the C content is preferably 0.55%, more preferably 0.50%, and further preferably 0.45%.
[0167] Si: 0.01~0.90%
[0168] Silicon (Si) deoxidizes steel in the steelmaking process. Si also increases the hardness of mechanical structural parts made from steel materials and improves the fatigue strength of mechanical structural parts. If the Si content is less than 0.01%, the above effects cannot be fully obtained even if the contents of other elements are within the range of this embodiment.
[0169] On the other hand, Si has a weak affinity for C. Therefore, if the Si content exceeds 0.90%, even if the contents of other elements are within the range of the present embodiment, C is more likely to segregate at the grain boundaries than in the grains in which Si is dissolved during heating. As a result, when the steel is subjected to high-frequency quenching in the manufacturing process of a machine structural component using the steel as a raw material, melt fracture is likely to occur in the steel.
[0170] Therefore, the Si content is 0.01 to 0.90%.
[0171] The lower limit of the Si content is preferably 0.02%, more preferably 0.05%, further preferably 0.08%, further preferably 0.10%.
[0172] The upper limit of the Si content is preferably 0.70%, more preferably 0.65%, further preferably 0.55%, further preferably 0.50%.
[0173] Mn: 0.50~1.70%
[0174] Manganese (Mn) deoxidizes steel in the steelmaking process. Mn also improves the hardenability of steel. Therefore, the hardness of mechanical structural parts made from steel as raw material is improved, and the fatigue strength of mechanical structural parts is improved. In addition, Mn has a strong affinity with C. Therefore, when heated, C remains in the grains in which Mn is solid-dissolved. Therefore, the segregation of C to the grain boundaries can be suppressed. As a result, when high-frequency quenching is performed on steel in the manufacturing process of mechanical structural parts made from steel as raw material, the occurrence of melt fracture can be suppressed. In addition, Mn bonds with S to form Mn sulfide. Therefore, Mn can suppress the formation of coarse FeS. As a result, the hot workability of steel during hot working is improved, and the heat-resistant working cracking resistance is improved. If the Mn content is less than 0.50%, even if the content of other elements is within the range of this embodiment, the above-mentioned effects cannot be fully obtained.
[0175] On the other hand, Mn lowers the melting point of the steel. Therefore, if the Mn content exceeds 1.70%, even if the contents of other elements are within the range of the present embodiment, when the steel is subjected to high-frequency quenching in the manufacturing process of the mechanical structure parts using the steel as the raw material, the resistance to melt cracking will also be reduced. In addition, if the Mn content exceeds 1.70%, even if the contents of other elements are within the range of the present embodiment, the hardness of the steel will be excessively increased. In this case, the machinability of the steel cannot be fully obtained.
[0176] Therefore, the Mn content is 0.50 to 1.70%.
[0177] The lower limit of the Mn content is preferably 0.70%, more preferably 0.80%, further preferably 0.85%, further preferably 0.90%.
[0178] The upper limit of the Mn content is preferably 1.65%, more preferably 1.60%, more preferably 1.55%, more preferably 1.50%, more preferably 1.48%, more preferably 1.45%, more preferably 1.43%, and more preferably 1.40%.
[0179] P: 0.030% or less
[0180] Phosphorus (P) is an impurity. P segregates at grain boundaries and lowers the melting point of steel. Therefore, when high-frequency quenching is performed on steel in the manufacturing process of mechanical structural parts using steel as a raw material, melt fracture is easily caused in the steel.
[0181] Therefore, the P content is set to 0.030% or less.
[0182] The P content is preferably as low as possible. However, excessive reduction in the P content will lead to increased manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the P content is more than 0%, more preferably 0.001%, and even more preferably 0.002%.
[0183] The upper limit of the P content is preferably 0.028%, more preferably 0.026%, further preferably 0.023%, further preferably 0.020%.
[0184] S: 0.200% or less
[0185] Sulfur (S) generates sulfides to improve the machinability of steel. As long as a small amount of S is contained, the above-mentioned effects can be obtained to a certain extent even if the contents of other elements are within the range of this embodiment.
[0186] However, S lowers the melting point of steel. Therefore, if the S content exceeds 0.200%, even if the contents of other elements are within the range of the present embodiment, the steel is prone to melt fracture when high-frequency quenching is performed on the steel in the manufacturing process of mechanical structural parts using the steel as a raw material.
[0187] Therefore, the S content is set to 0.200% or less.
[0188] The lower limit of the S content is preferably more than 0%, more preferably 0.001%, more preferably 0.005%, more preferably 0.010%, more preferably 0.015%, and still more preferably 0.020%.
[0189] The upper limit of the S content is preferably 0.150%, more preferably 0.120%, more preferably 0.095%, more preferably 0.080%, more preferably 0.075%, more preferably 0.055%, and more preferably 0.035%.
[0190] Bi: 0.0051~0.2500%
[0191] Bismuth (Bi) forms particles in the steel, and through the pinning effect, it suppresses the coarsening of the grains (austenite grains) in the steel during the heating of high-frequency quenching. As long as the grains can be kept fine, the reduction in the grain boundary area can be suppressed. Therefore, the average C concentration per unit grain boundary area is reduced, which can suppress the melt fracture during high-frequency quenching. Bi also improves the machinability of the steel. If the Bi content is less than 0.0051%, even if the content of other elements is within the range of this embodiment, the above-mentioned effect cannot be fully obtained.
[0192] On the other hand, if the Bi content exceeds 0.2500%, even if the contents of other elements are within the range of the present embodiment, coarse Bi particles are excessively generated in the surface region of the steel material. The coarse Bi particles in the surface region are likely to become the starting point of cracking during hot working in the manufacturing process of the steel material or during hot working in the manufacturing process of mechanical structural parts. Therefore, the heat working cracking resistance of the steel material is reduced.
[0193] Therefore, the Bi content is 0.0051 to 0.2500%.
[0194] The lower limit of the Bi content is preferably 0.0060%, more preferably 0.0070%, more preferably 0.0100%, more preferably 0.0150%, and still more preferably 0.0200%.
[0195] The upper limit of the Bi content is preferably 0.2000%, more preferably 0.1500%, more preferably 0.1250%, more preferably 0.1000%, more preferably 0.0900%, more preferably 0.0750%, and more preferably 0.0600%.
[0196] Al: 0.001~0.100%
[0197] Aluminum (Al) deoxidizes steel. If the Al content is less than 0.001%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0198] On the other hand, if the Al content exceeds 0.100%, Al forms coarse oxides even if the contents of other elements are within the range of the present embodiment. Coarse oxides reduce the fatigue strength of machine structural parts manufactured using steel materials.
[0199] Therefore, the Al content is 0.001 to 0.100%.
[0200] The lower limit of the Al content is preferably 0.002%, more preferably 0.003%, further preferably 0.005%, further preferably 0.010%.
[0201] The upper limit of the Al content is preferably 0.060%, more preferably 0.050%, more preferably 0.040%, more preferably 0.030%, and still more preferably 0.025%.
[0202] N: 0.0250% or less
[0203] Nitrogen (N) forms nitrides and / or carbonitrides in the manufacturing process of mechanical structural parts using steel as raw material, and performs precipitation strengthening on the steel. As a result, the fatigue strength of the mechanical structural parts manufactured using steel as raw material is improved. As long as a small amount of N is contained, the above-mentioned effect can be obtained to a certain extent even if the content of other elements is within the range of this embodiment.
[0204] On the other hand, if the N content exceeds 0.0250%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0205] Therefore, the N content is set to 0.0250% or less.
[0206] The preferred lower limit of the N content is more than 0%, more preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, more preferably 0.0020%, more preferably 0.0030%, and still more preferably 0.0040%.
[0207] The upper limit of the N content is preferably 0.0200%, more preferably 0.0190%, more preferably 0.0170%, more preferably 0.0150%, more preferably 0.0130%, and still more preferably 0.0100%.
[0208] O: 0.0050% or less
[0209] Oxygen (O) is an impurity. O forms oxides in steel, which reduces the fatigue strength of mechanical structural parts made of steel.
[0210] Therefore, the O content is set to 0.0050% or less.
[0211] The O content is preferably as low as possible. However, excessive reduction in the O content leads to increased manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the O content is more than 0%, more preferably 0.0001%, and further preferably 0.0002%.
[0212] The upper limit of the O content is preferably 0.0030%, more preferably 0.0025%, more preferably 0.0020%, more preferably 0.0015%, and further preferably 0.0012%.
[0213] The balance of the chemical composition of the steel material of this embodiment is composed of Fe and impurities. Here, impurities refer to substances mixed from raw materials such as ores and waste materials or the manufacturing environment when the steel material is manufactured industrially, and are substances that are intentionally contained and are allowed within a range that does not adversely affect the steel material of this embodiment.
[0214] [Optional Elements]
[0215] The chemical composition of the steel material of this embodiment may further contain one or more elements selected from the following elements in place of a portion of Fe:
[0216] Cr: 0~1.30%,
[0217] V: 0~0.200%、
[0218] Sn: 0~0.1000%,
[0219] Sb: 0~0.0500%,
[0220] As: 0~0.0500%、
[0221] Pb: 0~0.09%,
[0222] Mg: 0~0.0100%,
[0223] Ti: 0~0.0400%,
[0224] Nb: 0~0.0500%,
[0225] W: 0~0.4000%、
[0226] Zr: 0~0.2000%,
[0227] Ca: 0~0.0100%,
[0228] Te: 0~0.0100%,
[0229] B: 0~0.0050%,
[0230] Rare earth elements: 0~0.0100%,
[0231] Co: 0~0.0100%,
[0232] Se: 0~0.0100%,
[0233] In: 0~0.0100%,
[0234] Mo: 0~0.30%,
[0235] Cu: 0-0.50%,
[0236] Ni: 0-0.50%.
[0237] These optional elements are described below.
[0238] [About Group 1: Cr and V]
[0239] The chemical composition of the steel material of the present embodiment may further contain the following first group of elements in place of a portion of Fe. These elements are arbitrary elements and can improve the fatigue strength of machine structural parts.
[0240] [Group 1]
[0241] One or more selected from the following elements:
[0242] Cr: 0 to 1.30%, and
[0243] V: 0~0.200%.
[0244] Cr: 0~1.30%
[0245] Chromium (Cr) is an arbitrary element and may not be contained. In other words, the Cr content may be 0%.
[0246] When Cr is contained, that is, when the Cr content exceeds 0%, Cr improves the hardenability of the steel. Therefore, the hardness of the mechanical structural parts made of the steel as a raw material is improved, and the fatigue strength of the mechanical structural parts is improved. The above effect can be achieved to a certain extent as long as a small amount of Cr is contained.
[0247] However, if the Cr content exceeds 1.30%, sufficient machinability cannot be obtained in the steel material even if the contents of other elements are within the ranges of the present embodiment.
[0248] Therefore, the Cr content is 0 to 1.30%, and when contained, the Cr content is 1.30% or less.
[0249] The lower limit of the Cr content is preferably 0.01%, more preferably 0.05%, more preferably 0.10%, more preferably 0.12%, more preferably 0.14%, more preferably 0.16%, and more preferably 0.18%.
[0250] The upper limit of the Cr content is preferably 1.25%, more preferably 1.20%, more preferably 1.10%, more preferably 1.00%, and still more preferably 0.90%.
[0251] V: 0~0.200%
[0252] Vanadium (V) is an arbitrary element and may not be contained. That is, the V content may be 0%.
[0253] When V is contained, that is, when the V content exceeds 0%, V precipitates in the ferrite in the steel in the form of V precipitates during the manufacturing process of the mechanical structural parts using the steel as the raw material. As a result, the hardness of the ferrite in the steel is improved. As a result, the fatigue strength of the mechanical structural parts is improved. The above effect can be achieved to a certain extent as long as V is contained in a small amount.
[0254] However, if the V content exceeds 0.200%, the above-mentioned effect is saturated and the manufacturing cost increases.
[0255] Therefore, the V content is 0 to 0.200%, and when V is contained, the V content is 0.200% or less.
[0256] The lower limit of the V content is preferably 0.001%, more preferably 0.003%, more preferably 0.005%, more preferably 0.007%, more preferably 0.010%, more preferably 0.015%, and more preferably 0.020%.
[0257] The upper limit of the V content is preferably 0.180%, more preferably 0.160%, more preferably 0.140%, more preferably 0.120%, more preferably 0.100%, more preferably 0.080%, more preferably 0.050%, and more preferably 0.049%.
[0258] [About Group 2: Sn, Sb, As and Pb]
[0259] The chemical composition of the steel material of the present embodiment may further contain the following second group in place of a portion of Fe. These elements are all arbitrary elements and can improve the machinability of the steel material.
[0260] [Group 2]
[0261] One or more selected from the following elements:
[0262] Sn: 0~0.1000%,
[0263] Sb: 0~0.0500%,
[0264] As: 0 to 0.0500%, and
[0265] Pb: 0~0.09%.
[0266] Sn: 0~0.1000%
[0267] Tin (Sn) is an arbitrary element and may not be contained. In other words, the Sn content may be 0%.
[0268] When Sn is contained, that is, when the Sn content exceeds 0%, Sn segregates at the interface between the parent phase and the inclusions, making the steel embrittled. Therefore, the machinability of the steel is improved. The above effect can be achieved to a certain extent as long as Sn is contained in a small amount.
[0269] However, if the Sn content exceeds 0.1000%, Sn will be excessively segregated even if the contents of other elements are within the ranges of the present embodiment. In this case, the hot workability of the steel material will be reduced.
[0270] Therefore, the Sn content is 0 to 0.1000%, and when contained, the Sn content is 0.1000% or less.
[0271] The lower limit of the Sn content is preferably 0.0001%, more preferably 0.0010%, and further preferably 0.0020%.
[0272] The upper limit of the Sn content is preferably 0.0500%, more preferably 0.0100%, more preferably 0.0090%, more preferably 0.0080%, more preferably 0.0070%, more preferably 0.0060%, more preferably 0.0050%, and more preferably 0.0040%.
[0273] Sb: 0~0.0500%
[0274] Antimony (Sb) is an arbitrary element and may not be contained. That is, the Sb content may be 0%.
[0275] When Sb is contained, that is, when the Sb content exceeds 0%, Sb segregates at the interface between the parent phase and the inclusions, making the steel embrittled. Therefore, the machinability of the steel is improved. The above effect can be achieved to a certain extent as long as Sb is contained in a small amount.
[0276] However, if the Sb content exceeds 0.0500%, Sb will be excessively segregated even if the contents of other elements are within the ranges of the present embodiment. In this case, the hot workability of the steel material will be reduced.
[0277] Therefore, the Sb content is 0 to 0.0500%, and when contained, the Sb content is 0.0500% or less.
[0278] The lower limit of the Sb content is preferably 0.0001%, more preferably 0.0010%, and further preferably 0.0020%.
[0279] The upper limit of the Sb content is preferably 0.0400%, more preferably 0.0300%, more preferably 0.0200%, more preferably 0.0100%, more preferably 0.0080%, and still more preferably 0.0060%.
[0280] As: 0~0.0500%
[0281] Arsenic (As) is an arbitrary element and may not be contained. That is, the As content may be 0%.
[0282] When As is contained, that is, when the As content exceeds 0%, As segregates at the interface between the parent phase and the inclusions, making the steel embrittled. Therefore, the machinability of the steel is improved. The above effect can be achieved to a certain extent as long as As is contained in a small amount.
[0283] However, if the As content exceeds 0.0500%, As will be excessively segregated even if the contents of other elements are within the ranges of the present embodiment. In this case, the hot workability of the steel material will be reduced.
[0284] Therefore, the As content is 0 to 0.0500%, and when contained, the As content is 0.0500% or less.
[0285] The lower limit of the As content is preferably 0.0001%, more preferably 0.0010%, further preferably 0.0020%.
[0286] The upper limit of the As content is preferably 0.0100%, more preferably 0.0070%, more preferably 0.0060%, more preferably 0.0050%, and still more preferably 0.0040%.
[0287] Pb: 0~0.09%
[0288] Lead (Pb) is an arbitrary element and may not be contained. In other words, the Pb content may be 0%.
[0289] When Pb is contained, that is, when the Pb content exceeds 0%, Pb generates Pb particles in the matrix, making the steel embrittled. Therefore, the machinability of the steel is improved. The above effect can be achieved to a certain extent as long as Pb is contained in a small amount.
[0290] However, if the Pb content exceeds 0.09%, Pb particles are excessively generated even if the contents of other elements are within the ranges of the present embodiment. In this case, the hot workability of the steel material is reduced.
[0291] Therefore, the Pb content is 0 to 0.09%, and when contained, the Pb content is 0.09% or less.
[0292] The lower limit of the Pb content is preferably 0.01%, more preferably 0.02%, and further preferably 0.03%.
[0293] The upper limit of the Pb content is preferably 0.08%, more preferably 0.07%, further preferably 0.06%, further preferably 0.05%.
[0294] [About Group 3: Mg]
[0295] The chemical composition of the steel material of the present embodiment may further contain the following third group in place of a part of Fe.
[0296] [Group 3]
[0297] Mg: 0~0.0100%.
[0298] Magnesium (Mg) is an arbitrary element and may not be contained. In other words, the Mg content may be 0%.
[0299] When Mg is contained, that is, when the Mg content exceeds 0%, Mg deoxidizes the steel. The above-mentioned effect can be obtained to a certain extent as long as Mg is contained in a small amount.
[0300] However, if the Mg content exceeds 0.0100%, even if the contents of other elements are within the range of the present embodiment, Mg forms coarse oxides, which reduce the fatigue strength of machine structural parts manufactured using steel materials.
[0301] Therefore, the Mg content is 0 to 0.0100%, and when contained, it is 0.0100% or less.
[0302] The lower limit of the Mg content is preferably 0.0001%, more preferably 0.0003%, and further preferably 0.0005%.
[0303] The upper limit of the Mg content is preferably 0.0050%, more preferably 0.0045%, and further preferably 0.0040%.
[0304] [Group 4: Ti, Nb, W and Zr]
[0305] The chemical composition of the steel material of this embodiment may further contain the following fourth group in place of a portion of Fe. These elements are any elements that can form precipitates and refine the grains in the steel material by the pinning effect, thereby improving the toughness of the machine structural parts manufactured using the steel material as a raw material.
[0306] [Group 4]
[0307] One or more selected from the following elements:
[0308] Ti: 0~0.0400%,
[0309] Nb: 0~0.0500%,
[0310] W: 0 to 0.4000%, and
[0311] Zr: 0~0.2000%.
[0312] Ti: 0~0.0400%
[0313] Titanium (Ti) is an arbitrary element and may not be contained. That is, the Ti content may be 0%.
[0314] When Ti is contained, that is, when the Ti content exceeds 0%, Ti forms precipitates (carbides and / or carbonitrides). These precipitates refine the grains of the steel material through the pinning effect. As a result, the toughness of mechanical structural parts is improved. As long as a small amount of Ti is contained, the above effect can be achieved to a certain extent.
[0315] However, if the Ti content exceeds 0.0400%, the above-mentioned effect is saturated and the manufacturing cost increases.
[0316] Therefore, the Ti content is 0 to 0.0400%, and when contained, it is 0.0400% or less.
[0317] The lower limit of the Ti content is preferably 0.0001%, more preferably 0.0010%, further preferably 0.0050%, further preferably 0.0080%.
[0318] The upper limit of the Ti content is preferably 0.0300%, more preferably 0.0200%, further preferably 0.0175%, further preferably 0.0150%.
[0319] Nb: 0~0.0500%
[0320] Niobium (Nb) is an arbitrary element and may not be contained. That is, the Nb content may be 0%.
[0321] When Nb is contained, that is, when the Nb content exceeds 0%, Nb forms precipitates similarly to Ti, refines the grains of the steel material, and improves the toughness of mechanical structural parts. The above effects can be achieved to a certain extent as long as Nb is contained in a small amount.
[0322] However, when the Nb content exceeds 0.0500%, the above-mentioned effect is saturated and the manufacturing cost increases.
[0323] Therefore, the Nb content is 0 to 0.0500%, and when contained, it is 0.0500% or less.
[0324] The lower limit of the Nb content is preferably 0.0001%, more preferably 0.0010%, further preferably 0.0050%, further preferably 0.0080%.
[0325] The upper limit of the Nb content is preferably 0.0200%, more preferably 0.0175%, and further preferably 0.0150%.
[0326] W: 0~0.4000%
[0327] Tungsten (W) is an arbitrary element and may not be contained. That is, the W content may be 0%.
[0328] When W is contained, that is, when the W content exceeds 0%, W forms precipitates like Ti, refines the grains of the steel material, and improves the toughness of the machine structural parts. The above effect can be obtained to a certain extent as long as W is contained in a small amount.
[0329] However, if the W content exceeds 0.4000%, the above-mentioned effect is saturated and the production cost increases.
[0330] Therefore, the W content is 0 to 0.4000%, and when contained, it is 0.4000% or less.
[0331] The lower limit of the W content is preferably 0.0001%, more preferably 0.0050%, and further preferably 0.0500%.
[0332] The upper limit of the W content is preferably 0.3500%, more preferably 0.3000%, and further preferably 0.2000%.
[0333] Zr: 0~0.2000%
[0334] Zirconium (Zr) is an arbitrary element and may not be contained. In other words, the Zr content may be 0%.
[0335] When Zr is contained, that is, when the Zr content exceeds 0%, Zr forms precipitates similarly to Ti, refines the grains of the steel material, and improves the toughness of the machine structural parts. The above effects can be obtained to a certain extent as long as Zr is contained in a small amount.
[0336] However, if the Zr content exceeds 0.2000%, the above-mentioned effect is saturated and the production cost increases.
[0337] Therefore, the Zr content is 0 to 0.2000%, and when contained, it is 0.2000% or less.
[0338] The lower limit of the Zr content is preferably 0.0001%, more preferably 0.0010%, further preferably 0.0020%, further preferably 0.0050%.
[0339] The upper limit of the Zr content is preferably 0.1500%, more preferably 0.1000%, further preferably 0.0500%, further preferably 0.0100%.
[0340] [Group 5: Ca, Te, B, and rare earth elements (REM)]
[0341] The chemical composition of the steel material of the present embodiment may further contain the following fifth group in place of a portion of Fe. These elements are arbitrary elements and can improve the machinability of the steel material.
[0342] [Group 5]
[0343] One or more selected from the following elements:
[0344] Ca: 0~0.0100%,
[0345] Te: 0~0.0100%,
[0346] B: 0 to 0.0050%, and
[0347] Rare earth elements: 0~0.0100%.
[0348] Ca: 0~0.0100%
[0349] Calcium (Ca) is an arbitrary element and may not be contained. In other words, the Ca content may be 0%.
[0350] When Ca is contained, that is, when the Ca content exceeds 0%, Ca improves the machinability of the steel material. The above-mentioned effect can be obtained to a certain extent as long as Ca is contained in a small amount.
[0351] However, if the Ca content exceeds 0.0100%, even if the contents of other elements are within the range of the present embodiment, coarse oxides are formed. Coarse oxides reduce the fatigue strength of machine structural parts manufactured using the steel material as a raw material.
[0352] Therefore, the Ca content is 0 to 0.0100%, and when contained, it is 0.0100% or less.
[0353] The lower limit of the Ca content is preferably 0.0001%, more preferably 0.0005%, further preferably 0.0010%, further preferably 0.0015%.
[0354] The upper limit of the Ca content is preferably 0.0085%, more preferably 0.0070%, further preferably 0.0050%, further preferably 0.0030%.
[0355] Te: 0~0.0100%
[0356] Tellurium (Te) is an arbitrary element and may not be contained. That is, the Te content may be 0%.
[0357] When Te is contained, that is, when the Te content exceeds 0%, Te improves the machinability of the steel material. The above-mentioned effect can be obtained to a certain extent as long as Te is contained in a small amount.
[0358] However, if the Te content exceeds 0.0100%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0359] Therefore, the Te content is 0 to 0.0100%, and when contained, it is 0.0100% or less.
[0360] The lower limit of the Te content is preferably 0.0001%, more preferably 0.0003%, and further preferably 0.0010%.
[0361] The upper limit of the Te content is preferably 0.0090%, more preferably 0.0085%, further preferably 0.0080%, further preferably 0.0040%.
[0362] B: 0~0.0050%
[0363] Boron (B) is an arbitrary element and may not be contained. In other words, the B content may be 0%.
[0364] When B is contained, that is, when the B content exceeds 0%, B bonds with N to form BN, improving the machinability of the steel. B also segregates at the grain boundaries and contributes to grain boundary strengthening, improving the fatigue strength of mechanical structural parts made of steel as a raw material. The above effects can be achieved to a certain extent as long as B is contained in a small amount.
[0365] However, if the B content exceeds 0.0050%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0366] Therefore, the B content is 0 to 0.0050%, and when contained, it is 0.0050% or less.
[0367] The lower limit of the B content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0010%.
[0368] The upper limit of the B content is preferably 0.0040%, more preferably 0.0035%, and further preferably 0.0030%.
[0369] Rare earth elements (REM): 0~0.0100%
[0370] Rare earth elements (REM) are arbitrary elements and may not be contained. That is, the REM content may be 0%.
[0371] When REM is contained, that is, when the REM content exceeds 0%, REM improves the machinability of the steel material. The above-mentioned effect can be obtained to a certain extent as long as REM is contained in a small amount.
[0372] However, if the REM content exceeds 0.0100%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0373] Therefore, the REM content is 0 to 0.0100%, and when contained, it is 0.0100% or less.
[0374] The lower limit of the REM content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0010%.
[0375] The upper limit of the REM content is preferably 0.0090%, more preferably 0.0080%, further preferably 0.0070%, further preferably 0.0040%.
[0376] REM in this specification refers to one or more elements selected from scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71 as lanthanoid elements. The REM content in this specification refers to the total content of these elements.
[0377] [Group 6: Co, Se and In]
[0378] The chemical composition of the steel material of the present embodiment may further contain the following sixth group in place of a portion of Fe. These elements are any elements and can suppress decarburization of the steel material.
[0379] [Group 6]
[0380] One or more selected from the following elements:
[0381] Co: 0~0.0100%,
[0382] Se: 0 to 0.0100%, and
[0383] In: 0~0.0100%.
[0384] Co: 0~0.0100%
[0385] Cobalt (Co) is an arbitrary element and may not be contained. That is, the Co content may be 0%.
[0386] When Co is contained, that is, when Co exceeds 0%, Co suppresses decarburization of steel materials during the manufacturing process. The above-mentioned effect can be obtained to a certain extent as long as Co is contained in a small amount.
[0387] However, if the Co content exceeds 0.0100%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0388] Therefore, the Co content is 0 to 0.0100%, and when contained, it is 0.0100% or less.
[0389] The lower limit of the Co content is preferably 0.0001%, more preferably 0.0005%, further preferably 0.0010%, further preferably 0.0030%.
[0390] The upper limit of the Co content is preferably 0.0090%, more preferably 0.0080%, and further preferably 0.0070%.
[0391] Se: 0~0.0100%
[0392] Selenium (Se) is an arbitrary element and may not be contained. In other words, the Se content may be 0%.
[0393] When Se is contained, that is, when Se exceeds 0%, Se suppresses decarburization of the steel material during the manufacturing process. The above-mentioned effect can be obtained to a certain extent as long as Se is contained in a small amount.
[0394] However, if the Se content exceeds 0.0100%, hot working cracking may occur even if the contents of other elements are within the ranges of the present embodiment.
[0395] Therefore, the Se content is 0 to 0.0100%, and when contained, it is 0.0100% or less.
[0396] The lower limit of the Se content is preferably 0.0001%, more preferably 0.0010%, and further preferably 0.0020%.
[0397] The upper limit of the Se content is preferably 0.0090%, more preferably 0.0080%, and further preferably 0.0070%.
[0398] In: 0~0.0100%
[0399] Indium (In) is an arbitrary element and may not be contained. That is, the In content may be 0%.
[0400] When In is contained, that is, when In exceeds 0%, In suppresses decarburization of the steel material during the manufacturing process. The above-mentioned effect can be obtained to a certain extent as long as In is contained in a small amount.
[0401] However, if the In content exceeds 0.0100%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0402] Therefore, the In content is 0 to 0.0100%, and when contained, it is 0.0100% or less.
[0403] The lower limit of the In content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0010%.
[0404] The upper limit of the In content is preferably 0.0090%, more preferably 0.0080%, and further preferably 0.0070%.
[0405] [Group 7: Mo, Cu and Ni]
[0406] The chemical composition of the steel material of the present embodiment may further contain the following seventh group in place of a portion of Fe. These elements are any elements and can improve the fatigue strength of a machine structural component manufactured using the steel material as a raw material.
[0407] [Group 7]
[0408] One or more selected from the following elements:
[0409] Mo: 0~0.30%,
[0410] Cu: 0 to 0.50%, and
[0411] Ni: 0-0.50%.
[0412] Mo: 0~0.30%
[0413] Molybdenum (Mo) is an arbitrary element and may not be contained. That is, the Mo content may be 0%.
[0414] When Mo is contained, that is, when the Mo content exceeds 0%, Mo improves the fatigue strength of machine structural parts manufactured using the steel material as a raw material. The above effect can be obtained to a certain extent as long as Mo is contained in a small amount.
[0415] However, if the Mo content exceeds 0.30%, the hardness of the steel material becomes excessively high and the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0416] Therefore, the Mo content is 0 to 0.30%, and when contained, it is 0.30% or less.
[0417] The lower limit of the Mo content is preferably 0.01%, more preferably 0.05%, and further preferably 0.10%.
[0418] The upper limit of the Mo content is preferably 0.20%, more preferably 0.17%, and further preferably 0.15%.
[0419] Cu: 0~0.50%
[0420] Copper (Cu) is an arbitrary element and may not be contained. In other words, the Cu content may be 0%.
[0421] When Cu is contained, that is, when the Cu content exceeds 0%, Cu improves the fatigue strength of mechanical structural parts manufactured using the steel material as a raw material. The above effect can be obtained to a certain extent as long as Cu is contained in a small amount.
[0422] However, if the Cu content exceeds 0.50%, even if the contents of other elements are within the ranges of the present embodiment, melt fracture is likely to occur during induction hardening.
[0423] Therefore, the Cu content is 0 to 0.50%, and when contained, it is 0.50% or less.
[0424] The lower limit of the Cu content is preferably 0.01%, more preferably 0.02%.
[0425] The upper limit of the Cu content is preferably 0.20%, more preferably 0.10%, and further preferably 0.05%.
[0426] Ni: 0~0.50%
[0427] Nickel (Ni) is an arbitrary element and may not be contained. In other words, the Ni content may be 0%.
[0428] When Ni is contained, that is, when the Ni content exceeds 0%, Ni improves the fatigue strength of machine structural parts manufactured using steel materials as raw materials. The above effect can be obtained to a certain extent as long as Ni is contained in a small amount.
[0429] However, if the Ni content exceeds 0.50%, even if the contents of other elements are within the ranges of the present embodiment, melt fracture is likely to occur during induction hardening.
[0430] Therefore, the Ni content is 0 to 0.50%, and when contained, it is 0.50% or less.
[0431] The lower limit of the Ni content is preferably 0.01%, more preferably 0.02%.
[0432] The upper limit of the Ni content is preferably 0.20%, more preferably 0.10%, and further preferably 0.05%.
[0433] [About (Feature 2) Fn]
[0434] In the steel material of the present embodiment, Fn defined by the formula (1) is further 0.45 to 1.05.
[0435] Fn=C+(Si / 10)+(Mn / 5)-(5S / 7)+(5Cr / 22)+1.65V (1)
[0436] Here, the content of the corresponding element in mass % is substituted into each element symbol in formula (1). When the element is not contained, "0" is substituted into the corresponding element symbol.
[0437] Fn is an index of fatigue strength of mechanical structural parts manufactured using steel as raw material and machinability of steel. If Fn is less than 0.45, even if the steel satisfies characteristics 1, 3, and 4, sufficient fatigue strength cannot be obtained for mechanical structural parts manufactured using steel as raw material. On the other hand, if Fn exceeds 1.05, even if the steel satisfies characteristics 1, 3, and 4, the machinability of the steel will be reduced.
[0438] Therefore, Fn is 0.45 to 1.05.
[0439] The lower limit of Fn is preferably 0.50, more preferably 0.55, and further preferably 0.60.
[0440] The upper limit of Fn is preferably 1.00, more preferably 0.95, and even more preferably 0.90.
[0441] [(Feature 3) 0.08R Depth Position D 0.08R The number density of Bi particles at
[0442] Figure 2 : is a cross-sectional view perpendicular to the axial direction of the steel material of this embodiment. Figure 2 As shown, the cross section 10 of the steel material perpendicular to the axial direction is circular. The radius of the cross section 10 is defined as R. The surface D of the steel material is defined as 0.00R The position of the 0.08R depth of the starting point is defined as "0.08R depth position D 0.08R ”.
[0443] For the steel material of this embodiment, at the depth position D of 0.08R 0.08R At the same time, the number density of Bi particles with an equivalent circle diameter of 0.1 to 1.0 μm, i.e., fine Bi particles, is 15.00 particles / mm 2 The number density of Bi particles with an equivalent circle diameter of 10.0 μm or more, i.e., coarse Bi particles, is 0.25 particles / mm 2 the following.
[0444] like Figure 2 As shown, from the surface D of the steel 0.00R To 0.08R depth position D 0.08RThe area of the range from 0.040 to 0.060 is defined as the surface area SA. The surface area SA of the steel is an area near the surface of the steel that contacts a processing tool such as a mold or a roller during a hot working process in the manufacturing process of the steel, or a hot working process in the manufacturing process of a mechanical structure component using the steel as a raw material. Therefore, sufficient resistance to heat working cracking is required for the surface area SA. In addition, the surface area SA is also an area where the temperature is increased by high-frequency induction heating when high-frequency quenching is performed in the manufacturing process of a mechanical structure component using the steel as a raw material. Therefore, sufficient resistance to melt cracking is required for the surface area SA. Therefore, sufficient resistance to heat working cracking and sufficient resistance to melt cracking are required for the surface area SA of the steel.
[0445] As described above, during heating in high-frequency quenching, Bi particles with an equivalent circle diameter of 0.1 to 1.0 μm, i.e., fine Bi particles, suppress the coarsening of grains in the surface region SA by the pinning effect. If the number density of fine Bi particles in the surface region SA is increased, the grains can be kept in a fine state by the pinning effect. Therefore, the reduction in the grain boundary area can be suppressed, and the occurrence of melt fracture can be suppressed. If the 0.08R depth position D in the surface region SA is 0.08R The number density of fine Bi particles is 15.00 / mm 2 As described above, during heating in high-frequency quenching, the crystal grains can be kept fine, and as a result, sufficient resistance to melt cracking can be obtained in the steel material.
[0446] In addition, the surface area SA is subjected to a large external force from the hot working tool during hot working. During hot working, in the surface area SA of the steel material subjected to a large external force, Bi particles with an equivalent circle diameter of 10.0 μm or more, i.e., coarse Bi particles, become the starting point of hot working cracking. Therefore, it is preferable that the number density of coarse Bi particles in the surface area SA of the steel material is as low as possible. If the depth position D of 0.08R in the surface area SA is 0.08R The number density of coarse Bi particles is 0.25 / mm 2 Below this value, the number density of the coarse Bi particles in the surface layer region SA is sufficiently low, so that sufficient hot working crack resistance can be obtained in the steel material.
[0447] Therefore, the depth position D of 0.08R 0.08R The number density of fine Bi particles at the 2 The number density of coarse Bi particles is 0.25 / mm 2 the following.
[0448] 0.08R depth position D 0.08R The preferred lower limit of the number density of fine Bi particles at2 , more preferably 25.00 pieces / mm 2 , more preferably 30.00 pieces / mm 2 .
[0449] 0.08R depth position D 0.08R There is no particular upper limit on the number density of fine Bi particles at 0.08R. 0.08R The upper limit of the number density of fine Bi particles at the surface is, for example, 1000.00 particles / mm 2 .
[0450] 0.08R depth position D 0.08R The preferred upper limit of the number density of coarse Bi particles at 2 , more preferably 0.16 pieces / mm 2 , more preferably 0.12 pieces / mm 2 , more preferably 0.08 pieces / mm 2 .
[0451] Optimum depth position D is 0.08R 0.08R The number density of coarse Bi particles is low. 0.08R depth position D 0.08R The preferred lower limit of the number density of coarse Bi particles at 2 , more preferably 0.00 pieces / mm 2 .
[0452] It should be noted that in the surface area SA, there are not only the above-mentioned fine Bi particles and coarse Bi particles, but also Bi particles with an equivalent circle diameter of more than 1.0 μm and less than 10.0 μm. However, in the surface area SA, the number density of fine Bi particles and coarse Bi particles is more strongly related to hot working cracking and melt cracking during high-frequency quenching than the number density of Bi particles with an equivalent circle diameter of more than 1.0 μm and less than 10.0 μm. Therefore, in the present embodiment, the depth position D of 0.08R in the surface area SA is set to 0.08R The number density of fine Bi particles and coarse Bi particles at the site is used as an indicator of hot working cracking of steel and melt cracking during high-frequency quenching.
[0453] [(Feature 4) 0.65R depth position D 0.65R The number density of Bi particles at
[0454] Reference Figure 2 , the surface D of the steel 0.00R The position of the 0.65R depth of the starting point is defined as "0.65R depth position D 0.65R". The surface of the steel 0.00R The position of the 1.00R depth of the starting point is defined as "1.00R depth position D 1.00R ”.
[0455] In the steel material of this embodiment, at the 0.65R depth position D 0.65R At the same time, the number density of Bi particles with an equivalent circle diameter of 0.1 to 1.0 μm, i.e., fine Bi particles, is less than 15.00 particles / mm 2 The number density of Bi particles with an equivalent circle diameter of 10.0 μm or more, i.e., coarse Bi particles, exceeds 0.25 particles / mm 2 .
[0456] like Figure 2 As shown, from the 0.65R depth position D 0.65R To 1.00R depth position D 1.00R The area from the surface layer to the inner region CA is defined as the inner region CA. The inner region CA of the steel material is less susceptible to external forces during hot working and heat during high-frequency quenching than the surface layer SA. Therefore, compared with the surface layer SA, the inner region CA is not required to have resistance to heat working cracking and melting cracking. On the other hand, sometimes the inner region CA is subjected to cutting in the manufacturing process of mechanical structural parts using steel as raw materials. In this case, sufficient cutting performance is required for the inner region CA.
[0457] During cutting, the coarse Bi particles become the starting point for the chips to be peeled off from the main body of the steel. Therefore, the coarse Bi particles can improve the machinability of the steel. Therefore, it is preferred that the number density of the coarse Bi particles in the inner area CA is high. If the depth position D of 0.65R in the inner area CA is 0.65R The number density of coarse Bi particles exceeds 0.25 / mm 2 , sufficient machinability can be obtained in steel.
[0458] On the other hand, the influence of fine Bi particles on the machinability of steel is low. In addition, if the number density of fine Bi particles is high, the number density of coarse Bi particles is correspondingly reduced. Therefore, it is preferable that the number density of fine Bi particles is low in the inner region CA. If the number density of fine Bi particles is low at the depth position D of 0.65R in the inner region CA, the fine Bi particles are 0.65R The number density of fine Bi particles is less than 15.00 / mm 2 , coarse Bi particles are easily generated in the inner region CA. As a result, sufficient machinability can be obtained in the steel material.
[0459] Therefore, the depth position D of 0.65R 0.65R The number density of fine Bi particles at the surface is less than 15.00 / mm 2, the number density of coarse Bi particles exceeds 0.25 / mm 2 .
[0460] 0.65R depth position D 0.65R The preferred upper limit of the number density of fine Bi particles at 2 , more preferably 10.00 pieces / mm 2 , more preferably 7.50 pieces / mm 2 .
[0461] 0.65R depth position D is preferred 0.65R The number density of fine Bi particles is low. 0.65R depth position D 0.65R The preferred lower limit of the number density of fine Bi particles at 2 , more preferably 3.00 pieces / mm 2 , more preferably 1.50 pieces / mm 2 , more preferably 0.00 pieces / mm 2 .
[0462] 0.65R depth position D 0.65R The preferred lower limit of the number density of coarse Bi particles at 2 , more preferably 0.30 pieces / mm 2 , more preferably 0.40 pieces / mm 2 , more preferably 0.50 pieces / mm 2 .
[0463] 0.65R depth position D 0.65R There is no particular upper limit on the number density of coarse Bi particles at 0.65R. However, when the steel material satisfies the first and second characteristics, the depth position D 0.65R The upper limit of the number density of the coarse Bi particles at the position is, for example, 10.00 particles / mm 2 , more preferably 7.00 pieces / mm 2 .
[0464] It should be noted that in the inner region CA, not only the above-mentioned fine Bi particles and coarse Bi particles exist, but also Bi particles with an equivalent circle diameter of more than 1.0 μm and less than 10.0 μm exist. However, in the inner region CA, the number density of coarse Bi particles is more closely related to machinability than the number density of Bi particles with an equivalent circle diameter of more than 1.0 μm and less than 10.0 μm. Therefore, in the present embodiment, the number density of coarse Bi particles is more closely related to machinability than the number density of Bi particles with an equivalent circle diameter of more than 1.0 μm and less than 10.0 μm. 0.65R The number density of coarse Bi particles at φ 1 is used as an index of the machinability of the steel material.
[0465] [About 0.08R depth position D 0.08R Method for measuring the number density of fine Bi particles and coarse Bi particles at
[0466] 0.08R depth position D 0.08R The number density of fine Bi particles and the number density of coarse Bi particles at can be measured by the following method.
[0467] In the cross section parallel to the axial direction of the steel material and including the central axis of the steel material, the sample includes the depth position D of 0.08R. 0.08R In the collected test piece, the cross section parallel to the axial direction of the steel material and including the central axis of the steel material is used as the observation surface.
[0468] The observation surface was mirror-polished and ground. Using a scanning electron microscope (SEM), a depth position D including 0.08R on the mirror-polished observation surface was selected at a magnification of 1000 times. 0.08R The area of the observation area is set to 25.6mm 2 . To set the 0.08R depth position D 0.08R The observation region was selected so as to be arranged at the center position of the observation region. Furthermore, the observation region was divided into 624 parts (26×24 divisions) with a rectangular field of view of 202.5 μm×202.5 μm.
[0469] Based on the reflected electron images of each field of view obtained by SEM observation, the number density of coarse Bi particles and fine Bi particles is investigated using a particle analysis method of known image analysis. Specifically, based on the interface between the parent phase of the steel and the particles, the particles in the steel are determined. The particles described here are inclusions or precipitates. Image analysis is performed to determine the equivalent circular diameter of the determined particles. Specifically, the area of each determined particle is determined. The diameter of a circle with the same area as the determined area is taken as the equivalent circular diameter (μm) of the particle.
[0470] Among the particles observed in the reflected electron image obtained by the above-mentioned SEM observation, particles that meet the following conditions are determined as fine Bi particles: the equivalent circle diameter is 0.1 to 1.0 μm, and the result of point analysis of the composition of the particles using the energy dispersive X-ray analyzer (EDX: Energy Dispersive X-ray spectroscopy) possessed by the SEM is that the Bi content is 50% or more by mass%. In addition, among the particles observed in the reflected electron image obtained by SEM observation, particles that meet the following conditions are determined as coarse Bi particles: the equivalent circle diameter is 10.0 μm or more, and the result of point analysis of the composition of the particles using EDX is that the Bi content is 50% or more by mass%. The acceleration voltage of the EDX analysis is set to 20 kV. It should be noted that since Bi is a heavy element, it can be observed with high brightness in the reflected electron image. Therefore, Bi particles can be determined based on brightness.
[0471] Based on the total number of fine Bi particles identified in each field of view and the total area of the multiple fields of view constituting the above observation area (25.6 mm 2 ), find the depth position D of 0.08R 0.08R The number density of fine Bi particles at 2 Similarly, based on the total number of coarse Bi particles identified in each field of view and the total area of the above multiple fields of view (25.6 mm 2 ), find the depth position D of 0.08R 0.08R The number density of coarse Bi particles at 2 ).
[0472] [About 0.65R depth position D 0.65R Method for measuring the number density of fine Bi particles and coarse Bi particles at
[0473] 0.65R depth position D 0.65R The number density of fine Bi particles and the number density of coarse Bi particles at can be measured by the following method.
[0474] In the cross section parallel to the axial direction of the steel material and including the central axis of the steel material, the sample includes the depth position D of 0.65R. 0.65R In the collected test piece, the cross section parallel to the axial direction of the steel material and including the central axis of the steel material is used as the observation surface.
[0475] The observation surface was mirror-polished. Using SEM, a depth position D including 0.65R was selected on the observation surface after mirror-polishing at a magnification of 1000 times. 0.65R The area of the observation area is set to 25.6mm2 . To set the 0.65R depth position D 0.65R The observation region was selected so as to be arranged at the center position of the observation region. Furthermore, the observation region was divided into 624 parts (26×24 divisions) with a rectangular field of view of 202.5 μm×202.5 μm.
[0476] Based on the reflected electron images of each field of view obtained by SEM observation, the number density of coarse Bi particles and fine Bi particles is investigated using a particle analysis method of known image analysis. Specifically, the particles in the steel are determined based on the interface between the parent phase of the steel and the particles. The particles described here are inclusions or precipitates. Image analysis is performed to determine the equivalent circular diameter of the determined particles. Specifically, the area of each determined particle is determined. The diameter of a circle with the same area as the determined area is taken as the equivalent circular diameter (μm) of the particle.
[0477] Among the particles observed in the reflected electron image obtained by the above-mentioned SEM observation, particles that meet the following conditions are determined as fine Bi particles: the equivalent circle diameter is 0.1 to 1.0 μm, and the result of point analysis of the composition of the particles using EDX is that the Bi content is 50% or more by mass%. In addition, among the particles observed in the reflected electron image obtained by SEM observation, particles that meet the following conditions are determined as coarse Bi particles: the equivalent circle diameter is 10.0 μm or more, and the result of point analysis of the composition of the particles using EDX is that the Bi content is 50% or more by mass%. The acceleration voltage of EDX analysis is set to 20 kV. It should be noted that since Bi is a heavy element, it can be observed with high brightness in the reflected electron image. Therefore, Bi particles can be determined based on brightness.
[0478] Based on the total number of fine Bi particles identified in each field of view and the total area of the multiple fields of view constituting the above observation area (25.6 mm 2 ), find the depth position D of 0.65R 0.65R The number density of fine Bi particles at 2 Similarly, based on the total number of coarse Bi particles identified in each field of view and the total area of the above multiple fields of view (25.6 mm 2 ), find the depth position D of 0.65R 0.65R The number density of coarse Bi particles at 2 ).
[0479] [Effects of the steel material of this embodiment]
[0480] As described above, the steel material of the present embodiment satisfies characteristics 1 to 4. Therefore, the steel material can simultaneously obtain excellent resistance to melting cracking, excellent resistance to hot working cracking, and excellent machinability. In addition, for mechanical structural parts manufactured using the steel material as a raw material, high fatigue strength can be obtained.
[0481] [Preferred Applications and Shapes of the Steel Material of the Present Embodiment]
[0482] The steel material of this embodiment can be widely used as a raw material of mechanical structural parts, for example. The steel material of this embodiment is particularly suitable for the case where hot working such as hot forging, high-frequency quenching, and cutting are performed in the manufacturing process of mechanical structural parts. Among them, even if one or more of the hot working, high-frequency quenching, and cutting processes are not performed, the steel material of this embodiment can be used as a raw material of mechanical structural parts.
[0483] It should be noted that the cross section of the steel material perpendicular to the axial direction is circular. The diameter of the cross section of the steel material perpendicular to the axial direction is not particularly limited, and is, for example, 10 to 200 mm.
[0484] [Manufacturing method]
[0485] An example of a method for producing the steel material of the present embodiment will be described. The steel material satisfying characteristics 1 to 4 can be produced by a production method other than the production method described below. However, the production method described below is a preferred example of the method for producing the steel material of the present embodiment.
[0486] An example of the method for producing the steel material according to the present embodiment includes the following steps. It should be noted that step 3 is an arbitrary step and may not be performed.
[0487] (Process 1) Refining process
[0488] (Process 2) Casting process
[0489] (Process 3) Hot working process
[0490] Hereinafter, each step will be described.
[0491] [(Step 1) Refining step]
[0492] In the refining step, molten steel is produced having a chemical composition satisfying the above-mentioned characteristics 1 and 2. The refining step includes a primary refining step and a secondary refining step.
[0493] In the primary refining process, molten iron produced by a known method is subjected to refining in a converter to produce molten steel. In the secondary refining process, alloy elements are added to the molten steel to adjust the chemical composition of the molten steel so that it satisfies characteristics 1 and 2. Specifically, in the secondary refining process, while the molten steel is stirred by a known refining method, the components of the molten steel other than Bi are adjusted. Then, after Bi is added to the molten steel by a wire, the molten steel is stirred to adjust the Bi component. In the secondary refining process, the following conditions are met.
[0494] (Condition 1)
[0495] After Bi is added to the molten steel, the time t0 until the stirring is completed in the secondary refining step is set to be more than 15 minutes and less than 60 minutes.
[0496] (Condition 2)
[0497] The stirring power density ε of the molten steel after Bi is added to the molten steel is set to 10 to 100 W / t. Here, the stirring power density ε (W / t) is defined by the following formula (A).
[0498] ε=0.0285×Q×T / W×log(1+513.5×Z / V1)(A)
[0499] The gas flow rate (NL / min) blown into the ladle containing molten steel is substituted into Q in formula (A). The molten steel temperature (K) is substituted into T. The molten steel mass (t) is substituted into W. The molten steel depth (m) in the ladle is substituted into Z. The vacuum degree (torr) of the gas atmosphere containing the stirred molten steel is substituted into V1.
[0500] Condition 1 and Condition 2 are described below.
[0501] [Regarding condition 1: time t0]
[0502] In the secondary refining step, after Bi is added, the time t0 until the stirring in the secondary refining step is completed is more than 15 minutes and less than 60 minutes.
[0503] After Bi is added, if the time t0 until the stirring is completed in the secondary refining process is less than 15 minutes, Bi is not sufficiently diffused in the molten steel. In this case, coarse Bi particles are excessively generated in the produced steel. 0.08R The number density of coarse Bi particles at the position becomes excessively high.
[0504] On the other hand, after Bi is added, if the time t0 until the end of stirring in the secondary refining step is 60 minutes or more, Bi in the molten steel tends to aggregate. In this case, the number density of fine Bi particles in the produced steel material decreases. Therefore, at the depth position D 0.08R The number density of fine Bi particles at the location becomes excessively low.
[0505] In the secondary refining process, after Bi is added, when the time t0 until the end of stirring in the secondary refining process exceeds 15 minutes and is less than 60 minutes, Bi is sufficiently diffused in the molten steel. Therefore, on the premise of satisfying condition 2 and conditions 3 and 4 described later, the depth position D of 0.08R in the steel material is 0.08R and 0.65R depth position D 0.65R The number density of fine Bi particles and the number density of coarse Bi particles are within appropriate ranges.
[0506] It should be noted that after Bi was added, the temperature of the molten steel was 1510 to 1630°C until the stirring was completed in the secondary refining step.
[0507] [Regarding condition 2: stirring power density ε]
[0508] The stirring power density ε of the molten steel after Bi is added to the molten steel is 10 to 100 W / t.
[0509] If the stirring power density ε of the molten steel after Bi is added is less than 10 W / t, Bi is not sufficiently diffused in the molten steel. In this case, coarse Bi particles are excessively generated in the manufactured steel. 0.08R The number density of coarse Bi particles at the position becomes excessively high.
[0510] On the other hand, if the stirring power density ε of the molten steel after Bi is added exceeds 100 W / t, Bi in the molten steel becomes easy to aggregate. In this case, the number density of fine Bi particles in the manufactured steel material decreases. Therefore, at the depth position D 0.08R The number density of fine Bi particles at the location becomes excessively low.
[0511] If the stirring power density ε of the molten steel after Bi is added is 10 to 100 W / t, Bi will be fully diffused in the molten steel. Therefore, under the premise of satisfying condition 2 and conditions 3 and 4 described later, the depth position D of 0.08R in the steel material is 0.08R and 0.65R depth position D 0.65R The number density of fine Bi particles and the number density of coarse Bi particles are within appropriate ranges.
[0512] [(Process 2) Casting process]
[0513] In the casting step, molten steel is used to produce a cast slab by a known continuous casting method. The casting step is carried out under the following conditions.
[0514] (Condition 3)
[0515] When the solidification cooling rate at a depth of 15 mm from the surface in a cross section perpendicular to the longitudinal direction of the slab is defined as the surface layer solidification cooling rate, the surface layer solidification cooling rate is set to 550° C. / min or more.
[0516] (Condition 4)
[0517] For the cross section of the casting that is perpendicular to the length direction, when the cross section is rectangular, the solidification cooling rate at the midpoint between the casting surface and the center of the casting on the line at the center of the width of the long side of the rectangular cross section is defined as the internal solidification cooling rate. When the cross section is circular, the solidification cooling rate at the midpoint of the radius R (i.e., the R / 2 depth position) is defined as the internal solidification cooling rate. At this time, the internal solidification cooling rate is set to less than 100°C / min.
[0518] Condition 3 and Condition 4 are described below.
[0519] [Regarding condition 3: surface solidification cooling rate]
[0520] Bi particles are generated during solidification. That is, Bi particles are generated by crystallization. Therefore, in order to make the steel satisfy feature 3, it is preferred to accelerate the solidification cooling rate of the surface layer of the cast piece and solidify the steel before the Bi particles are coarsened. Therefore, in the casting process, the cooling rate of the cast piece in the mold of the continuous casting device is adjusted in such a way that the solidification cooling rate at a depth of 15 mm from the surface of the cast piece is 550°C / min or more.
[0521] Here, the cooling rate from the liquidus temperature to the solidus temperature in the temperature range of the steel in the casting process is defined as the solidification cooling rate (°C / min). In addition, as mentioned above, the solidification cooling rate at a depth of 15 mm from the surface of the cast piece is defined as the "surface solidification cooling rate". The surface solidification cooling rate is determined by the following method.
[0522] In the cross section perpendicular to the length direction of the cast piece manufactured by the continuous casting method, a test piece including a depth position of 15 mm from the surface of the cast piece is collected. For example, when the cross section perpendicular to the length direction of the cast piece is rectangular, a test piece including a depth position of 15 mm from the width center position of the surface of the cast piece (equivalent to the width center position of the surface of the long side when the cross section is rectangular) is collected. The surface of the test piece equivalent to the cross section perpendicular to the length direction of the cast piece is used as the observation surface. The 5mm×5mm area centered on the depth position of 15 mm from the surface of the cast piece in the observation surface is used as the observation area. In the observation area, the secondary dendrite arm spacing of 10 locations is measured, and the arithmetic mean thereof is set to λ2 (μm). The surface solidification cooling rate V (℃ / min) is calculated using the measured secondary dendrite arm spacing λ2 (μm).
[0523] V=(λ2 / 770) -1 / 0.41
[0524] The area at a depth of 15 mm from the surface of the cast piece solidifies during the process of passing through the mold (die) of the continuous casting device. Therefore, the surface solidification cooling rate can be adjusted by the cooling mechanism in the mold. The upper limit of the surface solidification cooling rate is not particularly limited. The preferred lower limit of the surface solidification cooling rate is 600°C / min or more, and the further preferred lower limit is 700°C / min or more. It should be noted that as a preferred casting speed for obtaining a surface solidification cooling rate of 550°C / min or more, 0.6m / min or less can be exemplified.
[0525] [Regarding condition 4: internal solidification cooling rate]
[0526] As described above, Bi particles are generated during solidification. Therefore, in order to make the steel satisfy feature 4, it is preferable to slow down the solidification cooling rate inside the cast piece and solidify the steel after the Bi particles are coarsened. Therefore, in the casting process, the cooling rate of the cast piece is adjusted so that the internal solidification cooling rate is 100°C / min or less.
[0527] Here, the internal solidification cooling rate based on the above definition is determined by the following method.
[0528] For the cross section perpendicular to the length direction of the cast piece manufactured by the continuous casting method, when the cross section shape is rectangular, collect the test piece of the midpoint between the cast piece surface and the cast piece center on the line containing the center of the width of the long side of the rectangular cross section, and when the cross section shape is circular, collect the test piece containing the midpoint of the radius R (R / 2 depth position). The surface of the test piece corresponding to the cross section perpendicular to the length direction of the cast piece is used as the observation surface. The 5mm×5mm area centered on the above-mentioned midpoint in the observation surface is used as the observation area. In the observation area, the secondary dendrite arm spacing of 10 locations is measured, and the arithmetic mean thereof is set to λ2 (μm). The internal solidification cooling rate V (℃ / min) is calculated using the measured secondary dendrite arm spacing λ2 (μm).
[0529] V=(λ2 / 770) -1 / 0.41
[0530] The internal solidification cooling rate can be adjusted, for example, by changing the size of the mold (die). Specifically, the internal solidification cooling rate can be adjusted by adjusting the area of the cross section of the mold. In addition, in the roller group arranged downstream of the mold of the continuous casting machine, a plurality of fluid nozzles for cooling the cast sheet are arranged between the rollers. Therefore, by adjusting the flow rate of the fluid (coolant represented by water, air, or a mixed fluid of coolant and air) ejected from these multiple fluid nozzles, the internal solidification cooling rate can be adjusted. The lower limit of the internal solidification cooling rate is not particularly limited, and the preferred lower limit is 10°C / min or more. The preferred upper limit is 50°C / min or less, and the further preferred upper limit is 25°C / min or less.
[0531] [(Process 3) Hot working process]
[0532] The hot working step is an optional step. That is, the hot working step may be performed or not. When the hot working step is performed, the cast piece produced in the casting step is hot worked to produce a steel material.
[0533] The hot working process may be, for example, only a known rough rolling process, or may include a known rough rolling process and a known finishing rolling process performed after the rough rolling process. In the rough rolling process, a steel billet is manufactured from a heated cast sheet or steel block, for example, by block rolling, or hot rolling using a continuous rolling mill after block rolling. In the finishing rolling process, for example, a steel material (steel bar) is manufactured by performing finishing rolling using a known continuous rolling mill on the heated steel billet. The heating temperature in the rough rolling process is, for example, 1000 to 1300°C. The heating temperature in the finishing rolling process is, for example, 1000 to 1300°C.
[0534] In the above-mentioned hot working process, the steel material is manufactured by hot rolling. However, the steel material may be manufactured by other hot working processes other than hot rolling. For example, the steel material may be manufactured by hot forging instead of hot rolling. In addition, the steel material may be manufactured by hot rolling and hot forging. Even when hot forging is performed in the hot working process, the heating temperature is, for example, 1000 to 1300°C.
[0535] The steel material of this embodiment can be manufactured through the above manufacturing process. It should be noted that, as described above, the hot working process can be omitted. In other words, the steel material of this embodiment can be a cast product (cast sheet).
[0536] [Method for manufacturing machine structural parts]
[0537] As described above, the steel material of this embodiment can be used as a raw material of a machine structural component. The method for manufacturing a machine structural component is well known, and for example, is as follows.
[0538] The steel material of this embodiment is hot worked to produce an intermediate product having a general shape of a machine structural component (for example, a crankshaft). The hot working is, for example, hot forging. The produced intermediate product is naturally cooled in the atmosphere.
[0539] The intermediate product after natural cooling is subjected to cutting to be cut into a given shape. The intermediate product after cutting is subjected to known high-frequency quenching (tempering omitted), or known high-frequency quenching and known tempering. Through the above steps, mechanical structural parts can be manufactured.
[0540] Example
[0541] The effect of the steel material of this embodiment will be described in more detail by way of examples. The conditions in the following examples are one condition example adopted to confirm the feasibility and effect of the steel material of this embodiment. Therefore, the steel material of this embodiment is not limited to this one condition example.
[0542] Steel materials having the chemical compositions shown in Tables 1-1 to 1-3 were produced.
[0543] [Table 1-1]
[0544] Table 1-1
[0545]
[0546] [Table 1-2]
[0547] Table 1-2
[0548]
[0549] [Table 1-3]
[0550] Table 1-3
[0551]
[0552] Specifically, the refining process (primary refining process and secondary refining process) was carried out using a 70-ton converter. In the primary refining process, molten iron produced by a known method was refined in a converter under the same conditions.
[0553] After the primary refining process, the secondary refining process was carried out. Specifically, the refining process using LF (Ladle Furnace) was carried out, and then the RH vacuum degassing process was carried out. Through these processes, the composition of elements other than Bi was adjusted. Then, Bi was further added to the molten steel through a wire, and the molten steel was stirred to adjust the composition of Bi.
[0554] After Bi was added to the molten steel, the time t0 (minutes) until the stirring was completed in the secondary refining process is shown in Table 2. In addition, the stirring power density ε (W / t) during stirring is shown in Table 2. It should be noted that after Bi was added to the molten steel, the molten steel temperature until the stirring was completed in the secondary refining process was 1510 to 1630° C. Molten steel was produced through the above steps.
[0555] [Table 2]
[0556] Table 2
[0557]
[0558] Molten steel was used to produce a cast slab (steel ingot) by continuous casting. The solidification cooling rate (°C / min) was adjusted during casting. The surface solidification cooling rate and the internal solidification cooling rate are shown in Table 2. It should be noted that the surface solidification cooling rate and the internal solidification cooling rate were obtained by the methods described in [Regarding Condition 3: Surface Solidification Cooling Rate] and [Regarding Condition 4: Internal Solidification Cooling Rate] above.
[0559] The produced ingot was subjected to hot working. Specifically, the ingot was subjected to rough rolling to produce a billet having a cross section of 180 mm×180 mm. The heating temperature of the ingot during the rough rolling was 1250°C.
[0560] Furthermore, the steel billet was subjected to hot forging equivalent to finish rolling to produce a steel material (steel bar) with a diameter of 97 mm. It should be noted that the heating temperature of the steel billet during hot forging is 1250°C. Forging was carried out using a pneumatic hammer (model 600HP) manufactured by Otani Machinery Manufacturing Co., Ltd. After the steel billet was heated at 1250°C for 1 hour, it was forged into a cross-section of 120 mm × 120 mm. Then, after heating at 1250°C for 1 hour again, it was forged in a manner that the cross-section became an octagon circumscribed with a circle with a diameter of 97 mm. Then, after heating at 1250°C for 1 hour again, it was forged into a steel bar (round steel) with a diameter of 97 mm and a circular cross-section. The steel material was manufactured through the above manufacturing process.
[0561] [Evaluation test]
[0562] The following evaluation tests were performed on the steel materials of each test number.
[0563] (Test 1) 0.08R depth position D 0.08R The number density of fine Bi particles and coarse Bi particles at
[0564] (Test 2) 0.65R depth position D 0.65R The number density of fine Bi particles and coarse Bi particles at
[0565] (Test 3) Hot working crack evaluation test
[0566] (Test 4) Melt fracture evaluation test
[0567] (Test 5) Cutting performance evaluation test (drill life test)
[0568] (Test 6) Fatigue strength evaluation test (rotational bending fatigue test)
[0569] Hereinafter, each evaluation test will be described.
[0570] [(Test 1) 0.08R depth position D 0.08R [Test on the number density of fine Bi particles and coarse Bi particles at
[0571] For each test number of steel, the above [about 0.08R depth position D 0.08R The depth position D at 0.08R was obtained by the method described in [Method for measuring the number density of fine Bi particles and coarse Bi particles at 0.08R]. 0.08R The number density of fine Bi particles at 2 ) and 0.08R depth position D 0.08R The number density of coarse Bi particles at 2 ). The results are shown in Table 2.
[0572] [(Test 2) 0.65R depth position D 0.65R [Test on the number density of fine Bi particles and coarse Bi particles at
[0573] For each test number of steel, the above [about 0.65R depth position D 0.65R The depth position D at 0.65R was obtained by the method described in [Method for measuring the number density of fine Bi particles and coarse Bi particles at 0.65R]. 0.65R The number density of fine Bi particles at 2 ) and 0.65R depth position D 0.65R The number density of coarse Bi particles at 2 ). The results are shown in Table 2.
[0574] [(Test 3) Hot working cracking evaluation test]
[0575] The surface of the steel material of each test number manufactured was observed. When the result of the observation was that two or more clear cracks were observed on the surface of the steel material per 1m of the length of the steel material, it was judged that hot working cracks had occurred. On the other hand, when the result of the observation was that two or more clear cracks were not observed on the surface of the steel material per 1m of the length of the steel material, it was judged that hot working cracks were suppressed. Here, clear cracks refer to cracks with a length of 3mm or more observed by the naked eye or using a simple magnifying glass.
[0576] The evaluation results of hot working cracks are shown in the "Hot Working Cracks" column of Table 2. "NG" indicates that hot working cracks occurred, and "OK" indicates that hot working cracks were suppressed.
[0577] [Regarding (Tests 4 to 6) Melt fracture evaluation test, machinability evaluation test, and fatigue strength evaluation test]
[0578] [Manufacturing of intermediate products simulating machine structure parts]
[0579] Heat treatment was performed to simulate hot forging in the manufacturing process of mechanical structure parts using the steel materials of each test number as raw materials. Specifically, the steel material was heated and kept at 1100°C for 30 minutes. Then, the steel material was naturally cooled in the atmosphere. Hereinafter, the steel material after the above heat treatment will be referred to as "simulated intermediate product of mechanical structure parts (or simply simulated intermediate product)". The simulated intermediate product of mechanical structure parts is a bar steel (round steel) with a diameter of 97 mm.
[0580] [(Test 4) Melt fracture evaluation test]
[0581] A test piece with a width of 10 mm, a thickness of 3 mm, and a length of 100 mm was prepared from the region including the surface region SA of the simulated intermediate product of the mechanical structure component by machining. The length direction of the test piece was parallel to the length direction of the simulated intermediate product. In addition, the central axis parallel to the length direction of the test piece coincided with the 0.08R depth position.
[0582] A quenching test simulating high-frequency quenching was performed on the test piece using a thermal cycle test apparatus manufactured by Fuji Denpa Koki Co., Ltd. Specifically, the test piece was heated to 1400°C at a heating rate of 100°C / second. Then, the test piece was kept at 1400°C for 15 seconds. Then, the test piece was water-cooled.
[0583] The water-cooled test piece was cut in the center of the length direction of the test piece along a direction perpendicular to the length direction. Then, the cut surface was used as the observation surface. The observation surface was mechanically polished. The mechanically polished observation surface was corroded by Picral reagent. The center position of the corroded observation surface was observed with a 400-fold optical microscope, and the presence or absence of melt fracture was confirmed by naked eye observation. The observation field was set to 250μm×400μm.
[0584] In the observation surface, when a region (corroded region) with a length of 5 μm or more is observed at the grain boundary, it is judged that melt fracture has occurred. A region with a width of 5 μm or more at the grain boundary refers to, for example, Figure 3 The area indicated by symbol 15 in FIG. Figure 4 As shown, when no corrosion area is observed at the grain boundary, it is judged that melt fracture is suppressed. The evaluation results of melt fracture are shown in the "Melting Fracture" column of Table 2. In the case where melt fracture occurs, it is indicated as "NG". In the case where melt fracture is suppressed, it is indicated as "OK".
[0585] [(Test 5) Cutting performance evaluation test (drill life test)]
[0586] A test piece for the machinability evaluation test was cut out from a simulated intermediate product of a mechanical structure component. Specifically, a drill bit was used to perforate an arbitrary position of the internal area CA of the cross section perpendicular to the length direction of the simulated intermediate product with a diameter of 97 mm. As a tool, a drill bit of model SD3.0 manufactured by Fujikoshi Co., Ltd. was used. As the perforation condition, the average feed rate per revolution was set to 0.25 mm / rev, and the perforation depth of one hole was set to 9 mm. The lubricant was a water-soluble cutting oil.
[0587] The drilling was carried out under the above drilling conditions, and the cutting performance of the steel was evaluated. The maximum cutting speed VL1000 (m / min) was used as an evaluation index. The maximum cutting speed VL1000 refers to the maximum value of the cutting speed of the drill that can drill a hole with a length of 1000 mm in terms of cumulative hole depth.
[0588] Based on the maximum cutting speed VL1000, the machinability was evaluated as follows.
[0589] VL1000 is 20 m / min or more: Excellent machinability ("OK")
[0590] VL1000 less than 20 m / min: low machinability ("NG")
[0591] In the column “Machinability” in Table 2, the evaluation results of “OK” and “NG” are shown.
[0592] [(Test 6) Fatigue strength evaluation test (rotational bending fatigue test)]
[0593] The fatigue strength was evaluated by the following test method using fatigue test specimens assuming that the machine structural parts were manufactured using steel materials as raw materials.
[0594] Produced from simulated intermediate products of mechanical structural parts Figure 5 The fatigue test piece shown. The fatigue test piece is a round rod test piece, the diameter D1 of the parallel part is 8 mm, and the diameter of the holding part is 12 mm. The fatigue test piece was made by machining from the R / 2 position (i.e., the center position of the radius) of the cross section perpendicular to the length direction of the simulated intermediate product of the mechanical structure component. The length direction of the fatigue test piece is parallel to the length direction of the simulated intermediate product. It should be noted that if the rotational bending fatigue strength of the test piece before high-frequency quenching is high enough, then for the test piece after high-frequency quenching, the rotational bending fatigue strength is also high enough, which is a technical common sense known to those skilled in the art.
[0595] The parallel portion of the fatigue test piece was finely polished to adjust the surface roughness. Specifically, the center line average roughness (Ra) of the surface in accordance with JIS B0601:2001 was within 3.0 μm, and the maximum height (Rmax) was within 9.0 μm.
[0596] Using fatigue test pieces, an Ono-type rotating bending fatigue test was conducted at room temperature (23°C), in an atmosphere, and under alternating conditions of a rotation speed of 3600 rpm. The fatigue test was conducted by varying the stress applied to a plurality of test pieces. 7 The highest stress without fracture after cycles was taken as fatigue strength (MPa).
[0597] If the obtained fatigue strength is 300 MPa or more, it is judged that sufficient fatigue strength is obtained. The results of the fatigue strength evaluation are shown in the "Fatigue Strength" column of Table 2. The case where the fatigue strength is 300 MPa or more is "OK", and the case where the fatigue strength is less than 300 MPa is "NG".
[0598] [Test results]
[0599] Tables 1-1 to 1-3 and 2 show the test results.
[0600] Referring to Tables 1-1 to 1-3 and 2, the chemical composition of the steels of test numbers 1 to 38 is appropriate and satisfies formula (1). In addition, the manufacturing conditions are also appropriate. Therefore, the steels of each test number satisfy characteristics 1 to 4. As a result, no hot working cracking and melt cracking were confirmed, and excellent hot working cracking resistance and excellent melt cracking resistance were obtained. In addition, the maximum cutting speed VL1000 of the steel is above 20m / min, and excellent machinability is obtained. In addition, the fatigue strength of the steel is above 300MPa, and the fatigue strength of mechanical structure parts manufactured using the steel as raw material is high.
[0601] On the other hand, Fn was less than 0.45 in Test Nos. 39 and 40. Therefore, the fatigue strength of the machine structural parts manufactured using the steel material was low.
[0602] In test numbers 41 and 42, Fn exceeded 1.05. Therefore, the machinability of the steel material was low.
[0603] In test numbers 43 and 44, the time t0 from the addition of Bi to the end of stirring was 15 minutes or less. 0.08R The number density of coarse Bi particles exceeds 0.25 / mm 2 The result was thermal cracking.
[0604] In test numbers 45 and 46, the time t0 from the addition of Bi to the end of stirring was 60 minutes or more. 0.08R The number density of fine Bi particles is less than 15.00 / mm 2 The result is melt fracture.
[0605] In test numbers 47 and 48, the stirring power density ε of the molten steel after adding Bi was less than 10 W / t. 0.08R The number density of coarse Bi particles exceeds 0.25 / mm 2 The result was thermal cracking.
[0606] In test numbers 49 and 50, the stirring power density ε of the molten steel after adding Bi exceeded 100 W / t. 0.08R The number density of fine Bi particles becomes less than 15.00 / mm 2 The result is melt fracture.
[0607] In test numbers 51 and 52, the surface layer solidification cooling rate during casting was less than 550°C / min. 0.08R The number density of fine Bi particles is less than 15.00 / mm 2 , 0.08R depth position D 0.08R The number density of coarse Bi particles exceeds 0.25 / mm 2 The result is thermal processing fracture and melt fracture.
[0608] In test numbers 53 and 54, the internal solidification cooling rate during casting exceeded 100°C / min. 0.65R The number density of fine Bi particles is 15.00 / mm 2 Above, 0.65R depth position D 0.65R The number density of coarse Bi particles is 0.25 / mm 2 As a result, the machinability of the steel material is low.
[0609] In test number 55, the Bi content was too low. Therefore, the depth position D 0.08R The number density of fine Bi particles is less than 15.00 / mm 2 , 0.65R depth position D 0.65R The number density of coarse Bi particles is 0.25 / mm 2 As a result, melt fracture occurs and the machinability of the steel material is reduced.
[0610] In test number 56, the Bi content was too high. Therefore, at the depth position D 0.08R The number density of coarse Bi particles exceeds 0.25 / mm 2 The result was thermal cracking.
[0611] The embodiments of the present invention have been described above. However, the above embodiments are merely examples for implementing the present invention. Therefore, the present invention is not limited to the above embodiments, and can be implemented by appropriately changing the above embodiments without departing from the gist thereof.
Claims
1. A steel material having a circular cross section perpendicular to the axial direction, wherein the chemical composition of the steel material comprises, in mass %, the following: C: more than 0.30% and less than 0.60%, Si: 0.01-0.90%, Mn: 0.50-1.70%, P: 0.030% or less, S: 0.200% or less, Bi: 0.0051~0.2500%, Al:0.001~0.100%、 N: 0.0250% or less, O: 0.0050% or less, Cr:0~1.30%、 V:0~0.200%、 Sn: 0~0.1000%, Sb: 0~0.0500%, As: 0~0.0500%、 Pb: 0~0.09%, Mg: 0~0.0100%, Ti: 0~0.0400%, Nb: 0~0.0500%, W:0~0.4000%、 Zr:0~0.2000%、 Ca: 0~0.0100%, Te: 0~0.0100%, B:0~0.0050%、 Rare earth elements: 0~0.0100%, Co: 0~0.0100%, Se: 0~0.0100%, In: 0~0.0100%, Mo: 0~0.30%, Cu: 0-0.50%, Ni: 0 to 0.50%, and The balance is Fe and impurities. Fn defined by formula (1) is 0.45 to 1.05, When the radius of the steel is defined as R, at a depth of 0.08R from the surface of the steel, The number density of fine Bi particles is 15.00 / mm 2 In the above, the fine Bi particles are Bi particles having an equivalent circle diameter of 0.1 to 1.0 μm. The number density of coarse Bi particles is 0.25 / mm 2 Hereinafter, the coarse Bi particles are Bi particles having an equivalent circle diameter of 10.0 μm or more. At a depth of 0.65R from the surface of the steel material, The number density of the fine Bi particles is less than 15.00 / mm 2 , The number density of the coarse Bi particles exceeds 0.25 / mm 2 , Fn=C+(Si / 10)+(Mn / 5)-(5S / 7)+(5Cr / 22)+1.65V (1) in, The content of the corresponding element in mass % is substituted into each element symbol in formula (1), and when the element is not contained, "0" is substituted into the corresponding element symbol.
2. The steel material according to claim 1, wherein: The chemical composition contains one or more elements selected from the following: Cr:0.01~1.30%、 V:0.001~0.200%、 Sn: 0.0001~0.1000%, Sb: 0.0001~0.0500%, As: 0.0001~0.0500%, Pb: 0.01~0.09%, Mg: 0.0001~0.0100%, Ti: 0.0001~0.0400%, Nb: 0.0001~0.0500%, W:0.0001~0.4000%、 Zr:0.0001~0.2000%、 Ca: 0.0001~0.0100%, Te: 0.0001~0.0100%, B:0.0001~0.0050%、 Rare earth elements: 0.0001~0.0100%、Co: 0.0001~0.0100%、Se: 0.0001~0.0100%、In: 0.0001~0.0100%、Mo: 0.01~0.30%、 Cu: 0.01-0.50%, Ni: 0.01~0.50%.
Citation Information
Patent Citations
Steel for die materials
JP2008169411A